The Determinants of Intergovernmental Grants in Portugal: a Public Choice Approach - Maria Manuel Pinho; Linda Veiga (European Regional Science Association (ERSA), 2004)
We use a large and unexplored dataset covering all mainland Portuguese municipalities from 1979 to 2001 to evaluate the impact of political forces in the allocation of grants from the central government to local authorities. Empirical results clearly show that, besides variables that proxy the social and economic development of municipalities, political variables also condition the granting system: (1) grants increase in municipal and legislative election years; (2) the larger the number of years a mayor has been in office the larger the amount of funds transferred to his municipality; (3) municipalities ruled by mayors that belong to the prime-minister's party are favored in the grants distribution process. Keywords: grants, intergovernmental relations, public choice, Portugal JEL classification: H77, D72, D78
Keywords: H77; D72; D78; 330; grants; intergovernmental relations; public choice; Portugal